Case report: Sideroblastic anemia with B-cell immunodeficiency, periodic fevers, and developmental delay: Three cases and a literature review - Chen, Xiangyuan; Fu, Fang; Mo, Xiaolan; Cheng, Suyun; Zeng, Huasong (Frontiers in Pediatrics, 2023)
Sideroblastic anemia with B-cell immunodeficiency, periodic fevers, and developmental delay (SIFD) is a serious autosomal recessive syndrome caused by biallelic mutations in cytosine–cytosine–adenosine (CCA) tRNA nucleotidyltransferase 1 (TRNT1). The main clinical features of SIFD are periodic fevers, developmental delay, sideroblastic or microcytic anemia, and immunodeficiency. Herein, we report three cases of SIFD with compound heterozygous variants of TRNT1. Patients 1 and 2 were siblings, they presented with periodic fevers, arthritis, low immunoglobulin A (IgA), bilateral cataracts, anemia, and neurodevelopmental and developmental delay. Patient 3 had severed clinical features with recurrent fever and infections. She was treated with infliximab and symptomatic treatments but without therapeutic effect. She received a stem cell transplantation of umbilical cord blood (UCB) but died of post-transplant infection and post-transplant graft-versus-host disease after 17 days of transplantation. Finally, a literature review revealed that TRNT1 variants differed among SIFD patients. Our cases and literature review further expand existing knowledge on the phenotype and TRNT1 variations of SIFD, and suggest that the early genomic diagnosis of TRNT1 is valuable to promptly assess bone marrow transplantation and TNF inhibitor treatments, which might be effective for the immunodeficiency and inflammation caused by SIFD.